Positive Expressive Writing, Fear of Childbirth and Childbirth Self-Efficacy: A Preliminary Study - Yesika Cahya Septiana; Luluk Fajria Maulida; Siti Nurhidayati; Hafi Nurinasari; Rufidah Maulina (Poltekkes Kemenkes Jakarta III, 2026)
to experience increased stress related to the childbirth process, which may lead to fear of childbirth (FOC). High levels of FOC negatively affect the childbirth process and overall birth experience. Fear of childbirth is known to be negatively correlated with childbirth self-efficacy, where better selfefficacy is associated with higher childbirth satisfaction. Expressive writing is a simple psychological intervention focused on emotional processing through writing and has been proven effective in reducing stress and anxiety among pregnant women. However, research examining the effects of expressive writing on FOC and childbirth self-efficacy among third-trimester pregnant women in Indonesia remains limited. Objectives: To examine the effect of expressive writing on fear of childbirth and childbirth self-efficacy among third-trimester pregnant women. Methods: This study employed a preexperimental design using a one-group pretest–posttest approach. A total of 26 third-trimester pregnant women were selected using accidental sampling. The expressive writing intervention was conducted for four consecutive days. FOC was measured using the W-DEQ version A, while childbirth self-efficacy was assessed using the CBSEI C-32. Data were analyzed using the paired ttest. Results: The results showed a significant reduction in fear of childbirth after the expressive writing intervention (p = 0.043). However, the increase in childbirth self-efficacy scores after the intervention was not statistically significant (p = 0.063). Conclusion: Expressive writing was effective in reducing fear of childbirth but did not demonstrate a significant effect on improving childbirth self-efficacy among third-trimester pregnant women.